Prediction and Treatment of Difficult Cases in Colorectal Endoscopic Submucosal Dissection - Yutaka Inada; Naohisa Yoshida; Munehiro Kugai; Kazuhiro Kamada; Kazuhiro Katada; Kazuhiko Uchiyama; Osamu Handa; Tomohisa Takagi; Hideyuki Konishi; Nobuaki Yagi; Yuji Naito; Naoki Wakabayashi; et al. (Gastroenterology Research and Practice)
Purpose. The aim of this study was to examine the characteristics of difficult cases and the learning curve in colorectal endoscopic submucosal dissection (ESD). Methods. We studied 518 colorectal tumors treated by ESD. Patients were divided into 2 groups such as the difficult ESD group and non-difficult ESD group in view of procedure time and procedure speed, respectively. The clinical features in each group were analyzed, and we also examined cases with severe fibrosis. Furthermore, we divided all cases into 5 periods according to experience of ESDs and investigated the rates of difficult and perforation cases. Results. In view of both procedure time and procedure speed, there were significant differences about mean tumor size, rates of severe fibrosis and perforation, and en bloc resection rate between the two groups. Severe fibrosis was detected in protruding tumors >40 mm in diameter. With respect to the learning curve, the rate of difficult and perforation cases decreased significantly in the late periods compared to the first period. Conclusions. Large tumor size, high rates of severe fibrosis and perforation, and low rate of en bloc resection are related with difficult ESD cases. The increasing of experiences can decrease the rate of difficult cases and perforation.